Climate Variability, Oceanography, Bowhead Whale Distribution, and Iñupiat Subsistence Whaling near Barrow, Alaska - Ashjian, Carin J.; Braund, Stephen R.; Campbell, Robert G.; George, J. C.; Kruse, Jack; Maslowski, Wieslaw; Moore, Sue E.; Nicolson, Craig R.; Okkonen, Stephen R.; Sherr, Barry F.; Sherr, Evelyn B.; Spitz, Yvette H. (SelectedWorks, 2010)
The annual migration of bowhead whales (Balaena mysticetus) past Barrow, Alaska, has provided subsistence hunting to Iñupiat for centuries. Bowheads recurrently feed on aggregations of zooplankton prey near Barrow in autumn. The mechanisms that form these aggregations, and the associations between whales and oceanography, were investigated using field sampling, retrospective analysis, and traditional knowledge interviews. Oceanographic and aerial surveys were conducted near Barrow during August and September in 2005 and 2006. Multiple water masses were observed, and close coupling between water mass type and biological characteristics was noted. Short-term variability in hydrography was associated with changes in wind speed and direction that profoundly affected plankton taxonomic composition. Aggregations of ca. 50–100 bowhead whales were observed in early September of both years at locations consistent with traditional knowledge. Retrospective analyses of records for 1984–2004 also showed that annual aggregations of whales near Barrow were associated with wind speed and direction. Euphausiids and copepods appear to be upwelled onto the Beaufort Sea shelf during E or SE winds. A favorable feeding environment is produced when these plankton are retained and concentrated on the shelf by the prevailing westward Beaufort Sea shelf currents that converge with the Alaska Coastal Current flowing to the northeast along the eastern edge of Barrow Canyon.